Lying under self-control depletion and time pressure - Serhiy Kandul; Apshara Naguleswaran (University of Neuchâtel, Institute of Economic Research (IRENE), 2019)
Dealing with temptations requires self-control. If lying for money constitutes a temptation, restricting people's self-control resources would enhance unethical behavior. We argue that the effect of the selfcontrol on lying depends on two things: 1) easiness to grasp the opportunity to lie, and 2) the amount of time available to decide. In an incentivized online experiment, we manipulate participants' self-control resources through an ego depletion task and allow them to misreport the outcome of a dice-roll with and without time pressure. We find evidence that ego depletion increases the fraction of truth-tellers under time pressure. Our findings suggest that when discovering the opportunities to lie is not trivial and people are constrained with the time, self-control depletion enhances people's ethical behavior.
Keywords: C91; D91; 330; Lying; Ego depletion; Self-control; Ethical behavior; Time pressure